Interleukin-10 responses from acute exercise in healthy subjects: A systematic review - Cabral-Santos, Carolina [UNESP]; de Lima Junior, Edson Alves; Fernandes, Isabela Maia da Cruz [UNESP]; Pinto, Rafael Zambelli; Rosa-Neto, José César; Bishop, Nicolette Charllote; Lira, Fábio Santos [UNESP] (Wiley, 2019)
Purpose: Interleukin 10 (IL-10) is a cytokine that plays a critical role with potent anti-inflammatory properties when produced during exercise, limiting host immune response to pathogens and preventing tissue damage. The purpose of this systematic review was to assess the response of IL-10 after acute exercise session in healthy adults. Methods: Databases of Ovid Medline (1978–2016), CINAHL (1998–2016), EMBASE (2003–2016), SportDiscus (1990–2016), and Web of Science library (1990–2016) were carefully screened. Clinical trials comparing exercise types in healthy individuals were included for pooled analysis. The trials of exercise were methodologically appraised by PEDro Scale. Results: Twelve randomized controlled and crossover trials containing 176 individuals were identified for inclusion. The Kruskal-Wallis test showed no significant differences between type of exercise and the corresponding values in IL-10 [X2(4) = 2.878; p = 0.449]. The duration of exercise was significantly correlated with increase in IL-10 changes (Pearson's r = 1.00, 95%CI: 0.015–0.042, p < 0.0001) indicating that 48% of the variation in IL-10 levels can be explained by the duration of the exercise performed. In addition, despite a linear increase, we did not find a significant correlation with the intensity of exercise and IL-10 changes (Pearson's r = 0.218, 95%CI: −0.554–0.042, p < 0.035). Conclusion: Overall, the duration of the exercise is the single most important factor determining the magnitude of the exercise-induced increase of plasma IL-10.
Keywords: acute exercise; anti-inflammatory response; inflammation; interleukin 10 (IL-10)